STUDY OF THE USE AND POTENTIAL OF DRUG INTERACTIONSIN THE TREATMENT OF HYPERTENSION PATIENTS AT X HOSPITALS CILACAP IN 2020 - Dwi Maryanti; Mika Tri Kumala Swandari (Universitas Muhammadiyah Kalimantan Timur, 2020)
Hypertension is a state of increasing systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90mmHg on 2 measurements with an interval of 5 minutes in a fairly calm state. Pharmacological management of hypertension refers to the Guideline Joint National Committee (JNC) 8 of 2014. The use of pharmacological therapy can cause problems, one of which is drug interactions. The complexity of using drugs tends to increase drug interactions. In this study, a potential drug interaction study was conducted to determine the magnitude of the potential interactions that might occur between drugs. The method used is descriptive method. The population in this study were medical records of hypertensive drug users diagnosed. Data analysis used univariate data analysis and the use of the Lexicom application. The results of the characteristics of hypertension drug users were 57,69% women and 42,31% men. Characteristics based on age were the youngest age 40 years (0.77%), 74 years old (0.77%) and the average age 61 (9.23%) years. The class of drugs used was 53.71% Calcium Channel Blocker, 28% Angiotensin Receptor Blocker, 8.57% Angiotensin Converting Enzyme, 8% Beta Blocker and 1.71% Diuretic. The severity of hypertension medication was moderate 63.11%, Major 3.88%, minor 33.01%. Based on the results obtained, the majority of women using hypertension drug characteristics were 58% and the average age was 61 (8.9%) years. The majority of the drugs used were 54% Calcium Channel Blockers with a moderate majority of 64%.